Synthesis of phosphorus‐containing flame‐retardant antistatic copolymers and their applications in polypropylene. Issue 12 (11th November 2014) - Li, Qi; Chen, Yiquan; Song, Xinpu; Xie, Yingpeng; Hou, Qiong; Shi, Guang
ABSTRACT By adjusting the molar ratios of antistatic monomer of octyl phenol ethylene oxide acrylate (denoted as AS), rigid monomer of methyl methacrylate (denoted as MMA), and flame‐retardant monomer of 2‐(phosphoryloxymethyl oxyethylene) acrylate (denoted as FR), a series of flame‐retardant antistatic copolymers poly (octyl phenol ethylene oxide acrylate‐co‐methyl methacrylate‐co‐phosphoryloxymethyl oxyethylene acrylate) (donated as AMF) were synthesized through radical polymerization. Among the obtained copolymers, two copolymers, AMF162 (the feed molar ratio of AS, MMA, and FR as 1 : 6 : 2) and AMF1104 (the feed molar ratio of AS, MMA, and FR as 1 : 10 : 4) with different concentrations were added into polypropylene (PP) to prepare PP‐AMF162 and PP‐AMF1104 series of composites. The thermal stability, limiting oxygen index, the antistatic property, and mechanical properties of PP composites were tested and analyzed. PP‐AMF162 series composites have excellent antistatic effect. When the AMF162 content was equal to or <15 wt %, the impact strength of PP‐AMF162 composites was higher than that of pure PP. The results indicated that copolymer AMF162 was a suitable flame‐retardant and antistatic additive for PP. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41677.